Integrasi pendidikan karakter dalam pelajaran penyesuaian mahluk hidup dengan lingkungannya (adaptasi) di MIN 2 Jombang - Ni’matul Izza (Jurnal Biogenerasi, 2022)
Discussions about character education are always interesting from a theoretical and practical point of view. In this study, the author will explore the concept of character education and integration in the subject of adaptation of living things to their environment (adaptation) at MIN 2 Jombang. Because MIN 2 Jombang is one of the schools trying to implement a comprehensive education model in every lesson. By using a descriptive qualitative approach based on field research, this research tries to reveal the integrated form of character values ​​in the subject of adaptation of living things to their environment (adaptation). This study demonstrates the integration of teacher character values ​​through the stages of planning, implementation and closing. At each stage, the teacher develops material by integrating the values ​​of religious character, discipline, tolerance, independence, honesty, confidence, cooperation, and creativity.